1994
DOI: 10.1126/science.7939713
|View full text |Cite
|
Sign up to set email alerts
|

Cytoskeletal Functions During Drosophila Oogenesis

Abstract: Organismal morphogenesis is driven by a complex series of developmentally coordinated changes in cell shape, size, and number. These changes in cell morphology are in turn dependent on alterations in basic cytoarchitecture. Elucidating the mechanisms of development thus requires an understanding of the cytoskeletal elements that organize the cytoplasm of differentiating cells. Drosophila oogenesis has emerged as a versatile system for the study of cytoskeletal function during development. A series of highly co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
110
2
6

Year Published

1997
1997
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(120 citation statements)
references
References 65 publications
2
110
2
6
Order By: Relevance
“…Fusomes and ring canals, which are known to be characteristics of cystocyte division (Cooley and Theurkauf, 1994;Heming, 2003), were observed in ovaries of ICs (Fig. 2a), suggesting that emerging callows had already begun cystocyte division.…”
Section: Early Oogenesis: Fusome and Ring Canal Formationmentioning
confidence: 97%
See 1 more Smart Citation
“…Fusomes and ring canals, which are known to be characteristics of cystocyte division (Cooley and Theurkauf, 1994;Heming, 2003), were observed in ovaries of ICs (Fig. 2a), suggesting that emerging callows had already begun cystocyte division.…”
Section: Early Oogenesis: Fusome and Ring Canal Formationmentioning
confidence: 97%
“…Fusomes function as anchors to settle the dividing cystocytes into a follicle (i.e., a set of one oocyte and sister nurse cells). Then, fusomes become ring canals to transfer the protein 8 and mRNA synthesized in nurse cells into an oocyte (Cooley and Theurkauf, 1994). These cytoskeletal structures are detectable during follicle formation but finally disappear before vitellogenesis (Gutzeit et al, 1993;Tanaka and Hartfelder, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…These proteins are characterized by the presence of a motif of ϳ50 amino acids, which is repeated two to seven times and invariably contains two adjacent glycine residues. This motif is called the kelch repeat (Bork and Doolittle, 1994;Cooley and Theurkauf, 1994). Among members of this family, kelch, SPE-26, calicin, and ␣-scruin are synthesized as cytoskeletal components during germ cell differentiation, and they occur in membrane-associated dense structures (Xu and Cooley, 1993;Varkey et al, 1995;von Bülow et al, 1995;Way et al, 1995b).…”
Section: Enc-1 Is a Member Of The Kelch Family Of Proteins And Interamentioning
confidence: 99%
“…In the case of ␣-scruin, there are six kelch repeats at the N terminus and six kelch repeats at the C terminus that are responsible for ␣-scruin-actin cross-linking activity that stabilizes Limulus sperm acrosomal microfilaments (Owen and De Rosier, 1993;Schmid et al, 1993Schmid et al, , 1994. Because it has been suggested that kelch repeats identify a family of actin-binding proteins (Cooley and Theurkauf, 1994;Knowles and Cooley, 1994), and ENC-1 contains six of these repeats in the C-terminal half of the protein, we sought to examine the ability of ENC-1 to interact with the actin cytoskeleton. ENC-1 associates with the actin cytoskeleton (Fig.…”
Section: Enc-1 Is a Member Of The Kelch Family Of Proteins And Interamentioning
confidence: 99%
“…Approximately 70 different ABPs have been characterized, but new members are still being discovered (Pollard, 1993). Recently, a new family of actin-binding proteins with sequences homologous to the Drosophila kelch protein has emerged (Xue and Cooley, 1993;Cooley and Theurkauf, 1994). The Drosophila kelch protein is localized to large, actin-rich intercellular ring canals, which regulate cytoplasmic transport from nurse cells to the developing oocyte within the egg chamber.…”
Section: Introductionmentioning
confidence: 99%